The challenge of maintaining social economy principles over the long term: the case of TUSGSAL - Bernardo, Valeria; Hernández Adell, Ismael; Serrano Robles, Eloi (REVESCO. Revista de Estudios Cooperativos, 2023)
Social economy organisations are at an important moment from an economic and social point of view. New business models, the role of innovation, attention to stakeholders, social and environmental impact, as well as the governance system are central to consolidate and add value to their external and internal environment. Internally, it is particularly important to pay the necessary attention to the people and the social economy principles that motivated the creation of the organisation. In this sense, the self-management of worker-owned companies is closely linked to the capacity to integrate social economy principles into the organisation. The understanding and adoption of these principles by the members of the company is a key factor for its good performing and viability. However, over time, the integration of social economy principles can become distorted and thus generate tensions that negatively affect the organisation. This article looks at some of the variables that can affect the eventual loss of this concept, such as seniority, gender, or the professional group within the company. To this end, a case study is carried out in the labour company TUSGSAL by means of a survey and focus groups that provide new evidence to the debate on the management of worker-owned companies.
Keywords: Social economy; self-management; Cooperative principles; Labour society; Governance; Degeneration thesis